Congenital hamartoma of the arrector pili muscle. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
A 6-month-old baby girl was first observed for the presence since birth of an asymptomatic, slightly hyperpigmented lesion of the left hemithorax. The family history was negative for similar lesions. The physical examination showed a hyperchromic lesion of about 8 x 6 cm (Fig. 1), with irregular margins; to a close-up view the lesion showed clear hypertrichosis (Fig. 2). On palpation with intense finger pressure a tremor as temporary contraction of muscle groups was appreciated. A skin biopsy showed in the reticular dermis a proliferation of elongated and extended in various directions smooth muscle fibers, surrounded by collagen (Fig. 3); the hair follicles were hypertrophic and the epidermis was hyperpigmented. These clinical and histological findings confirmed the diagnosis of congenital hamartoma of the arrector pili muscle.